Opinion of Umar Bin Khattab About Child Education and Curriculum - Fauzi Ananda (Education Achievement: Journal of Science and Research, 2023)
Umar bin Khattab became caliph through the process of deliberation by Abu Bakr with leading companions. This is done to prevent the possibility of disputes and divisions among Muslims. The method taken by Abu Bakr turned out to be acceptable to the people and they immediately gave allegiance to Umar bin Khattab. Umar then called himself the Caliphs of Rasulullah and Amir al-Mu'minin. Umar's relatively long reign, which was 10 years, was used to expand the territory of the Islamic daulah and carry out various development programs during Umar bin Khattab's Islamic rule covering the Arabian Peninsula, Palestine, Syria, Persia and Egypt. He also made efforts to improve state administration by following the Persian model, namely dividing the territory into provinces. Apart from that, several departments were also formed, regulation of payment systems and land taxes, separation of judicial and executive powers by establishing court institutions, establishing public works offices, establishing Bait al-Mal, printing currency, and determining the year of hijrah. When Abu Bakr served as caliph, Umar always provided assistance and support for the policies carried out by Abu Bakr, so that it seemed that the government at that time was held by two people. Shortly before Abu Bakr died, he appointed Umar as his successor after consulting with other friends. The attempt to widen the Islamic territory that had been carried out by Abu Bakr was continued by Umar with glorious results. The Islamic region at the time of Umar included Iraq, Persia, Syria, Egypt and Barqah.